2021
DOI: 10.1155/2021/5528144
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Deep Learning Techniques on Chest X-Ray and CT Scan Identification of COVID-19

Abstract: Pneumonia is an infamous life-threatening lung bacterial or viral infection. The latest viral infection endangering the lives of many people worldwide is the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes COVID-19. This paper is aimed at detecting and differentiating viral pneumonia and COVID-19 disease using digital X-ray images. The current practices include tedious conventional processes that solely rely on the radiologist or medical consultant’s technical expertise that are limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…Investigators have developed many models to detect COVID-19 during the past two years and have shown that there is a role for AI in detecting COVID-19 [ 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 277 , 278 , 279 , 280 , 281 ]. The 184 technical papers reviewed in this study provide up-to-date knowledge on the usage of AI techniques in detecting COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have developed many models to detect COVID-19 during the past two years and have shown that there is a role for AI in detecting COVID-19 [ 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 277 , 278 , 279 , 280 , 281 ]. The 184 technical papers reviewed in this study provide up-to-date knowledge on the usage of AI techniques in detecting COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…These automated tools using cost-effective imaging modalities assist to address COVID-19 by preventing false negative reports, and can be used in the case of scarcity or non-availability of RT-PCR test kits in rural areas. Researchers have reported exhaustive studies using imaging modalities for the detection of COVID-19 [ 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Although these review papers have shown the significance of deep learning and machine leaning algorithms for automated detection, this paper explores the following key points in association with detection: The state-of-the-art AI techniques (deep neural network (DNN) and hand-crafted feature learning (HCFL) based models) used to detect COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Several overviews into the application of CNN techniques to aid in COVID-19 diagnosis have been conducted and we refer the reader to Refs. [ [35] , [36] , [37] ] for more details.…”
Section: Related Workmentioning
confidence: 99%
“…Contrarily, health workers need to receive proper training to collect PCR samples, while the processing and generation of CT or X-ray images are relatively easy. Therefore, the computer-aided COVID-19 recognition method has significant practical value, which helps reduce the burden of RT-PCR and speed up diagnosis efficiency [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%